2016
DOI: 10.1111/apt.13662
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: effect of fibre supplementation on chronic idiopathic constipation in adults

Abstract: This meta-analysis demonstrates that fibre is moderately effective, but also causes moderate gastrointestinal side effects. However, these findings need to be treated with caution due to a high risk of bias. Accordingly, further large, methodologically rigorous trials are required, before any definitive recommendation regarding its risk-benefit profile can be made. PROSPERO registration number CRD42014007005.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
1
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 59 publications
4
65
1
8
Order By: Relevance
“…Constipation has long been associated with a low fiber intake, and a typical low ­FODMAP diet can often lack fiber content. Nevertheless, a recent meta-analysis showed that there was low evidence on the importance of a high fiber diet in treating constipation: only 44% of RCTs demonstrated a significant increase in stool frequency and only 2 studies showed fiber-enhanced stool consistency [35]. In our study, we did not find a worsening of constipation despite the low FODMAP diet followed by patients with IBS and CD.…”
Section: Discussioncontrasting
confidence: 66%
“…Constipation has long been associated with a low fiber intake, and a typical low ­FODMAP diet can often lack fiber content. Nevertheless, a recent meta-analysis showed that there was low evidence on the importance of a high fiber diet in treating constipation: only 44% of RCTs demonstrated a significant increase in stool frequency and only 2 studies showed fiber-enhanced stool consistency [35]. In our study, we did not find a worsening of constipation despite the low FODMAP diet followed by patients with IBS and CD.…”
Section: Discussioncontrasting
confidence: 66%
“…Some studies found that prebiotics had a positive effect in constipated patients. Christodoulides et al [34] suggested that fiber was moderately effective for chronic idiopathic constipation in adults. Suares et al [35] also reported that soluble fiber might be more beneficial than insoluble fiber in constipated patients in alleviating straining, pain on defecation, improving stool consistency, and other constipation-related symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Suares and Ford, 56 which included six randomised controlled trials (RCTs) of soluble and insoluble fibre, found evidence of limited benefit overall in CIC, but suggested that soluble fibre was more effective than placebo, and led to improvements in individual symptoms. A further systematic review with meta‐analysis by Christodoulides and colleagues 57 also suggested that soluble fibre was effective for treating CIC, but highlighted that it may also cause unwanted gastrointestinal side effects, such as increased flatulence. Overall, the quality of evidence was low and the findings should be interpreted cautiously, due to a high risk of bias among all included studies.…”
Section: Managementmentioning
confidence: 99%